Discovery of a follistatin-derived myostatin inhibitory peptide. Issue 3 (1st February 2020) - Saitoh, Mariko; Takayama, Kentaro; Hitachi, Keisuke; Taguchi, Akihiro; Taniguchi, Atsuhiko; Tsuchida, Kunihiro; Hayashi, Yoshio
Graphical abstract: Abstract: Follistatin is well known as an inhibitor of transforming growth factor (TGF)-β superfamily ligands including myostatin and activin A. Myostatin, a negative regulator of muscle growth, is a promising target with which to treat muscle atrophic diseases. Here, we focused on the N -terminal domain (ND) of follistatin (Fst) that interacts with the type I receptor binding site of myostatin. Through bioassay of synthetic ND-derived fragment peptides, we identified DF-3, a new myostatin inhibitory 14-mer peptide which effectively inhibits myostatin, but fails to inhibit activin A or TGF-β1, in an in vitro luciferase reporter assay. Injected intramuscularly, DF-3 significantly increases skeletal muscle mass in mice and consequently, it can serve as a platform for development of muscle enhancement based on myostatin inhibition.